PENGARUH PENGENDALIAN DIRI DAN PERILAKU BELAJAR TERHADAP TINGKAT PEMAHAMAN PENGANTAR AKUNTANSI (Studi Empiris Pada Mahasiswa Program Studi Akuntansi Fakultas Ekonomi Universitas Prof. Hazairin SH Kota Bengkulu) - Riswandi, Pedi (Universitas Dehasen Bengkulu, 2015)
Pedi Riswandi; The purpose of this study was to determine the effect of self-control and behavioral study of the level of understanding of the accounting introductory accounting students of the University Prof. Hazarin city of Bengkulu. This type of research used in this research is quantitative descriptive research that seeks to said solving the existing problems based on the data and presents the data, analyze and interpret. The object of this research is accounting S1 student class of 2011 and 2012. The results of self control and significant influence on the level of understanding of accounting, as shown by the coefficient of 0.136 at a significant level of 0.007. Learning behavior and no significant effect on the level of understanding of accounting, as shown by the coefficient of 0.058 at a significant level of 0.420, the rejection of this hypothesis means learning behavior variables can not be used as benchmarks in the level of understanding of accounting. Restraint and Behavior Learning and were significant influence on the level of understanding of accounting that values Nagelkerke pseudo R-square of 0.968 This means that the variable self-control and learning behavior can be explained in this study amounted to 96.8% while the remaining 3.2% is explained by Other variables that were not included in this study.Key words: self-control, learning behavior